Theoretical Preparation of Fencers at the Stage of Previous Basic Development - Yuriy, Briskin; Maryan, Pityn; Olha, Zadorozhna; Oleksandr, Vaulin (Journal of Sports Research, 2015)
The article presents the results of a survey of fencers at the stage of previous basic development, aimed at determination of preparedness for various information blocks. There was established that general level of theoretical preparedness of fencers for different blocks of knowledge from 3,5 to 5,8 points. Questionnaire consisted of five blocks of questions: "The history of the origin and development of fencing", "Competitive activity", "Technique and Tactics", "Basic theory and methodology of athletes training", "Olympism". Correct answers were evaluated by varying the number of points depending on the level of difficulty.